The impact of mergers and acquisitions on the individual and the resulting affect upon everyday task performance - Young, Elaine (2005)
Mergers and acquisitions (M&A) have become an increasingly common reality of organisational life (Buono and Bowditch 1989). Although much has been written about the economic, financial and strategic aspects of M&A, it is only relatively recently that research attention has turned to the role and contribution of human factors. There is limited research of what happens to the corporate culture during mergers and acquisitions and even less mention of the impact upon the people who get 'restructured'.